Home country bias in product evaluation: the complementary roles of economic and socio-psychological motives - Verlegh, Peeter W J (Journal of International Business Studies, 2007)
Consumers often are positively biased in their evaluations of domestic products vs foreign alternatives. This study establishes economic and socio-psychological motives for this home country bias. Building on social identity theory, this paper shows that home country bias is in part driven by a need for self-enhancement. This influence is stronger for consumers who identify more strongly with their own country, and is complementary to the effect of consumer ethnocentrism, which provides an economic motivation for home country bias. The framework is supported in empirical studies conducted in the Netherlands and in the USA.